USE OF ANOVA STATISTICAL METHOD IN EVALUATION OF TOFU WASTEWATER USED FOR SPIRULINA CULTURE MEDIUM ENRICHED WITH UREA AND NaHCO3 - Mustamina Maulani; Gabriella Jasmine; Rosmalia Dita Nugraheni; Maman Djumantara; Asri Nugrahanti; Bayu Satiyawira; Cahaya Rosyidan; Lisa Samura; Harin Widiyatni; Pauhesti Pauhesti (INDONESIAN JOURNAL OF URBAN AND ENVIRONMENTAL TECHNOLOGY, 2023)
Indonesia has a large amount of liquid waste originating from the tofu industry. Currently, the treatment of tofu industrial wastewater is carried out using both anaerobic and aerobic methods, but both methods still have several weaknesses. In this study, the tofu industrial wastewater was utilized as a culture medium for Spirulina sp. to provide economic value from wastewater that can be used as bioethanol, pharmaceuticals, and food products rich in omega 3, chlorophyll, carotenoids. Aim: The growth of Spirulina sp. is closely related to the availability of macro and micronutrients as nutrients and the influence of environmental conditions, so this study was aimed to see the best variation of the addition of urea and NaHCO3 as additional nutrients to maximize growth and cell density of Spirulina sp. with tofu industrial wastewater media. Methodology and Results: This study was done by culvitating Spirulina sp in the growth media, measuring the Optical Density (OD), and analyzing quantitatively and using ANOVA on IBM SPSS Statistics version 20. The study indicated that adding urea and NaHCO3 to Spirulina sp. had no effect on cell density and growth rate. Treatment with addition of urea 0.36 g/500 ml without additional of NaHCO3 had the highest growth rate, 0.00852/day, and the highest cell density value on Spirulina sp. growth. Conclusion, significance, and impact study: The tofu liquid waste can be used as a new alternative used as fertilizer because in the liquid tofu waste, it provides the nutrients needed by Spirulina sp.